Quasi-ultrafine particles promote cell metastasis via HMGB1-mediated cancer cell adhesion. (January 2020) - Gao, Rui; Sang, Nan
Abstract: With increasingly severe air pollution, the aggravated health risks of particulate matter, especially ultrafine particles, are emerging as an urgent and sensitive topic. Considering the heterogeneity and complexity of ultrafine particles, there is insufficient evidence about their toxic effects and possible molecular mechanisms. To address this question, we analyzed the emission characteristics of quasi-ultrafine particles collected during winter in a typical coal-burning city, Taiyuan, and confirmed their contribution to lung cancer cell adhesion and metastasis. For the specific mechanism, we revealed that the endocytosis of quasi-ultrafine particles stimulated the release of HMGB1, induced NFκB-facilitated proinflammatory cytokine production through the interaction of HMGB1 with RAGE, and resulted in cancer-endothelial cell adhesion. These findings remind us of the potential effects of anthropogenic quasi-ultrafine particle pollution and provide a theoretical reference for the mitigation of tumorigenesis in a severe particulate matter contaminated environment. Graphical abstract: Image 1 Highlights: Quasi-ultrafine particles promote lung cancer cell adhesion and metastasis. The endocytosis of quasi-ultrafine particles stimulates the release of HMGB1. Release of HMGB1 induced inflammation results in cancer-endothelial adhesion.